Investigação experimental de metacontingências: separação do produto agregado e da conseqüência individual - Pereira, João Mariano Cenacchi (2008)
The present study s aim was to build an experimental analog of metacontingencies. The experiment started with on adult (P1) working on a computer. At each trial 4 numbers were presented on a row and the participant would type 4 numbers on a row underneath. If the sum on each column (which was not showed) was an odd number, points (exchanged by money at the end of the session) were added on a counter on the screen. Points would be subtracted for each column with an even number as the sum. A second participant was introduced when P1 s behavior was stable. Both participants worked under the same contingencies, sharing the computer screen (each side showed one of the participant s trial) and mouse. Once their behavior stabilized, experimental manipulations were added to answer the following questions: Interlocking behavioral contingencies involving both participants and their aggregate product would be selected if a consequence was made contingent on the aggregate product? What would happen when new generations of participants were introduced? The following experimental contingency was introduced: when the sum of the 4 numbers typed by one participant was larger than the sum of the numbers typed by the other, bonus points were added (in a box on the screen) for both participants. Bonuses were added independently of the points added or subtracted. A new participant substituted the oldest one when a stability criterion was met. All experimental contingencies remained the same when new generations were added. Two experiments were conducted. Results of Experiment 1, with 6 participants (6 generations) suggested the selection of a metacontingency: The dyads P3/P4, P4/P5, and P5/P6 systematically behaved producing the aggregate product and consequent bonuses. But the exam of these participant s response topographies indicated that another possible interpretation was that the behavior of one participant alone (who typed the same high numbers on every trial), independent of the other, produced the aggregate product. Minor changes on the screen to make the bonuses more salient and an increase on the magnitude of bonus points were introduced on Experiment 2. Once again results suggested that selection of metacontingencies occurred for 3 (of 7) dyads whose behavior consistently produced bonuses. The analysis of these participants response topographies added to this interpretation. Discussion of the present experiment emphasizes the feasibility of building experimental analogs of metacontingencies